Vitamin A Reduces the Mortality of Animals with Induced Liver Fibrosis by Providing a Multi-level Body Defense System - Bozhkov, Anatoly; Novikova, Anna; Klimova, Elena; Ionov, Igor; Akzhyhitov, Rustam; Kurhuzova, Nataliia; Bilovetska, Svitlana; Moskalov, Vitalii; Haiovyi, Stanislav (My University, 2022)
Liver diseases remain the most important medical and biological problem. Works devoted to the study of the vitamin A role have shown conflicting results of its effect on the fibrosis development. We tested the hypothesis that an increase of the copper content in the liver, an example of which is Wilson's disease, shifts the balance in the redox system towards pro-oxidants, which leads to the antioxidant systems inhibition, including a decrease in the vitamin A content; this affects the levels of liver function regulation and the development of fibrosis. Methods: In animals with Cu-induced liver fibrosis, neutrophil activity, the immunocompetent cells content, the activity of alanine aminotransferase and g-glutamylaminotransferase, the content of urea and creatinine in blood serum, as well as the vitamin A content in the liver, copper ions and its regenerative potential were determined. Results: It was found that three consecutive injections of copper sulfate to animals with an interval of 48 h between injections led to the death of 40% of the animals, and 60% showed resistance. The content of vitamin A in “resistant” animals at the beginning of the development of the fibrosis was reduced by 4 times compared to the control, the functional activity of the liver was somewhat reduced, and a connective tissue capsule was formed around the liver lobes in 75% of the animals. If animals with the initial stage of liver fibrosis received daily vitamin A at a dose of 300 IU/100 g of body weight, which was accompanied by its multiple increase in the liver (15 times on day 14), the mortality of animals decreased by almost 7 times, the functional activity of the liver did not differ from control. In the blood of these animals, the number of leukocytes, granulocytes, and monocytes was increased and phagocytic activity was increased. At the same time, the connective tissue capsule was developed more intensively than in animals receiving only copper sulfate, and was detected in 91% of the animals. Fragments of the liver, even more than in the case of fibrosis, lost the ability to regenerate in culture. Conclusion: We came to the conclusion that vitamin A leads to the connective tissue “specialization” formation of the liver and triggers vicious circles of metabolism and includes several levels of regulation systems. Further studies of the vitamin A effect mechanisms on the liver with fibrosis will allow the use of this antioxidant in the treatment
Vitamin A Reduces the Mortality of Animals with Induced Liver Fibrosis by Providing a Multi-level Body Defense System / Anatoliy Bozhkov, Anna Novikova, Elena Klimova, Igor Ionov, R Akzhyhitov, Nаtalia Kurhuzova, Svitlana Bilovetska, Vitalii Moskalov, Stanislav Haiovyi // Journal of Clinical and Experimental Hepatology, 2022. – Vol. Xxx. –| No. xxx | xxx. – P. 1–15
Keywords: Cu-індукований фіброз, вітамін A, регенерація печінки.; Cu-induced fibrosis, vitamin A, liver regeneration